TATA KELOLA REKAM MEDIS BERBASIS ELEKTRONIK DALAM MENUNJANG PELAPORAN OPERASI DENGAN MENGGUNAKAN METODE AGILE - Tasya, Asfa Hani; Setiani, Tanty; Syahidin, Yuda; Yunengsih, Yuyun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
For registration and reporting of operating patients at the Hermina Arcamanik Bandung hospital, manual recording is still done using paper forms, so stored data can be damaged or lost. The purpose of this study was to determine the governance of electronic-based medical records in supporting operational reporting using agile methods. The system developed for registration of surgical patients is based on a web, intending to make it easier for officers to record operating patients, minimize work time, and store data in the cloud service so that operating patient data is not damaged or lost. Development of a system for registering and reporting surgical patients at the Hermina Arcamanik Bandung hospital using the Agile method is very suitable for short-term projects because this method will be very adaptable if changes occur in a project. The system that has been made is tested using the black-box testing method. Researchers hope that the system built will be able to solve problems that often occur with the damage or loss of operational reporting documents